Properties, Detection Mechanism and Applications of AuNPs-Based Sensors in Virus Detection - Liu, Xinye (Transactions on Materials, Biotechnology and Life Sciences, 2024)
After the outbreak of COVID-19 pandemic, infections caused by viruses have been proved to be one of the greatest global burdens that causes significant morbidity and mortality over the world. Detecting the virus as early as possible can help achieve early diagnosis of the disease. This will help doctors grasp the precious time of treating patients. Therefore, the rapid and accurate detection of viral pathogens is crucial for the effective control in the spreading of diseases, especially during such global pandemics. In the recent years, varies types of gold nanoparticles (AuNPs) based sensors have emerged since AuNPs have shown great potential in the field of viral diagnostics. This review aims to provide an overview of AuNP-based virus detection strategies. It mainly covers the properties of AuNPs, the detection mechanism, and the applications of these methods, such as colorimetric detection, surface plasmon resonance biosensors, fluorescent detection, and electrochemical detection. This work will contribute to promoting the application of AuNPs in virus diagnosis and detection.